2022
DOI: 10.3390/ijms23042110
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of New Gemifloxacin Schiff Base (GMFX-o-phdn) Metal Complexes and Evaluation of Their Antimicrobial Activity against Some Phyto- or Human Pathogens

Abstract: Four novel ligand-metal complexes were synthesized through the reaction of Fe(III), pleaseCo(II), Zn(II), and Zr(IV) with Schiff base gemifloxacin reacted with ortho-phenylenediamine (GMFX-o-phdn) to investigate their biological activities. Elemental analysis, FT-IR, 1H NMR, UV-visible, molar conductance, melting points, magnetic susceptibility, and thermal analyses have been carried out for insuring the chelation process. The antimicrobial activity was carried out against Monilinia fructicola, Aspergillus fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 65 publications
(82 reference statements)
0
30
0
Order By: Relevance
“…These data indicated that CIP ligated as monodetate through the oxygen atom of the COO − group [ 44 , 48 ]. Additionally, the IR spectrum of the HMC ligand shows a very strong band at 1674 cm −1 assignable to the stretching vibration of the cyclic ester ν (C=O); this band is shifted to lower values ( Table 2 ), indicating the coordination of HMC through the oxygen atom of the carbonyl group [ 25 , 26 , 27 , 28 ]. The presence of the broad bands in the range 3489–3411 cm −1 confirms the presence of H 2 O in all complexes [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These data indicated that CIP ligated as monodetate through the oxygen atom of the COO − group [ 44 , 48 ]. Additionally, the IR spectrum of the HMC ligand shows a very strong band at 1674 cm −1 assignable to the stretching vibration of the cyclic ester ν (C=O); this band is shifted to lower values ( Table 2 ), indicating the coordination of HMC through the oxygen atom of the carbonyl group [ 25 , 26 , 27 , 28 ]. The presence of the broad bands in the range 3489–3411 cm −1 confirms the presence of H 2 O in all complexes [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data of the TG and DTG curves of the compounds are listed in Table 5 . The TG-DTG analyses of CIP were studied before [ 28 , 34 ]. Decomposition of HMC started at 50 °C and finished at 600 °C, with two stages.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations